Chemical bonding - Winter, Mark J.; Oxford University Press (Oxford ; New York : Oxford University Press, 2007)
This series of short texts provides accessible accounts of a range of essential topics in chemistry. Written with the needs of the student in mind, the Oxford Chemistry Primers offer just the right level of detail for undergraduate study, and will be invaluable as a source of material commonly presented in lecture courses yet not adequately covered in existing texts.
All the basic principles and facts in a particular area are presented in a clear and straightforward style, to produce concise yet comprehensive accounts of topics covered in both core and specialist courses.
This short text is intended for first-year undergraduates and introduces some concepts of chemical bonding in a clear, descriptive, and essentially non-mathematical fashion. The book addresses aspects of atomic orbital structure and uses this to develop a discussion of the bonding in diatomic and polyatomic molecules using Lewis dot structures, hybrid orbital, and molecular orbital methods. The prediction of molecular shape is addressed through the VSEPR method.
Atomic structure -- Lewis molecular structures -- Diatomic molecules -- Molecular geometry : VSEPR rules -- Hybrid orbital description of bonding -- The MO approach and polyatomic molecules.
Includes bibliographical references (pages [91]) and index.
Keywords: Chemical bonds